ANALISIS MUTU LAYANAN UNIT REKAM MEDIS BERDASARKAN KEPUASAN PELANGGAN INTERNAL DENGAN MENGGUNAKAN METODE SERVICE QUALITY DAN QUALITY FUNCTION DEPLOYMENT DI RSD KALISAT JEMBER - Ayu Widya Arizona; Nugroho Setyo Wibowo; Dian Damayanti (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2014)
ABSTRACTURM (Unit Rekam Medis) is one the healthy facilities headed by medical record chief. The head of medicalrecord has the authority to manage everything related to URM. RSD Kalisat is one of state hospitals in Jemberwhich has a vision as the pioneer hospital with the best quality and reachable for everyone. The quality of URMplays important role to support the quality of the hospital. One of the ways to measure the quality of URM isby using quality and quality function deployment method. This research is aimed to get the information aboutthe quality service of medical record based on internal patient satisfactory in medical record at RSD kalisatby using quality and Quality Function Deployment (QFD). From the result of the analysis, we have conclusion as the following; 1) there are some variables influence the quality servicen of five dimension, such as: thestrategic place of URM building from the ambulatory care,the strategic place of URM building from the longterm care, thestorage room of medical record equipment, the number of employments, communication service, the repidity of medical record file, the accuracy of medical record, the appropriateness of the information, medical record employee readiness, the accuracy if taking off the medical record file, the employee friendlines,the safety of medical record, the attitude of the employee dealing with the nurse. 2) The satisfactory of nusetoward to URM service is good enuogh. 3) The expecatation of ”communication” with high score 4,60 andthe expectation of ”the distance between URM building from ambulatory care” with the lowest 4,26. 4) Thepriority related to nurse necessary needed to focus by URM dealing with medical record employee readinesswhich has normalize raw weight value 0,0588. 5) The action priority for URM employee is ”internal andexternal training” which has the higher normalized contribution normalized contribution value0,2144Keywords: Quality, Quality Service, Quality Function Deployment, Medical Record